Aplicação da técnica de emissão acústica em ensaios de desgaste erosivo - Tiboni, Gustavo Borges (2011)
The erosive wear caused by impact of solid particles against a surface is a tribological phenomenon present in many segments of the industry, such as transportation, aerospace, mining, power generation, among others. The most usual method to set the wear rate is by measuring the mass loss of the material. In order to apply one technique with potential to determine the rate of erosion wear, this study developed a dedicated equipment and conducted preliminary erosion tests monitored by nondestructive testing known as acoustic emission technique (AE). This can be defined as a technique able to detect mechanical waves generated by the release of elastic energy accumulated in the material. Erosion testes were performed in order to evaluate the ability of equipment to collect data from AE and to correlate these data with the wear of the specimens. Samples of low carbon steel eroded by the impact of angular aluminum oxide particles suspended in air at three different velocities: 45, 57 and 67 m/s. The impact angle between the particles and the sample was set at 30 degrees and the test temperature at approximately 20°C. The wear rate has changed with the velocity in accordance with the kinetic energy of the particles and the AE parameter RMS showed sensitivity to the variation of particle impact velocity and to the wear of the sample eroded. The rate of AE signals collected over time correlated with the flow of particles striking the sample, and with the parameters of energy, rise time and duration of the signal.